﻿The effectiveness of Soderm® – forte gel and a new injectable dosage form of Rexod® in the complex treatment of experimental periodontitis in rats - Pavel A. Galenko-Yaroshevsky; Kristina V. Tseluiko; Valeriy K. Leontev; Mark A. Zadorozhniy; Viktor L. Popkov; Anait V. Zelenskaya; Sergey A. Babichev; Andrey V. Zadorozhniy; Sonya V. Meladze (Research Results in Pharmacology, 2022)
Introduction: Insufficient effectiveness of traditional drug therapy in a treatment of patients with chronic generalized periodontitis, as well as high social significance of this problem, determines the need to search for new drugs and their compositions aimed at solving it. Aim of the study: To increase the efficacy of complex treatment of periodontitis with the administration of Soderm®-Forte gel and a new injectable form of Rexod®. Materials and methods: Experiments were performed in 50 male Wistar rats. Experimental periodontitis (EP) was simulated by ligation of the necks of lower incisors. We studied the animals with intact periodontium, untreated EP, and when traditional drug therapy (TDT), as well as the combinations of TDT with Soderm®-Forte gel and additionally with the new injectable dosage form (NIF) of Rexod® were administered. The general condition, behavior, nutrition and body weight of the animals were evaluated. The Schiller-Pisarev test and the Muhlemann-Cowell bleeding index were used, and the amount of crevicular fluid (CF) was measured. The contamination of the marginal gum with microorganisms was determined. Results and discussion: The TDT in EP has a moderate therapeutic effect, which does not lead to a sufficiently high pharmacotherapeutic effect, whereas the combinations of TDT with Soderm®-Forte and, to a greater extent, TDT with Soderm®-Forte and NIF of Rexod® have high therapeutic efficacy, which is statistically confirmed by a sharp decrease in the amount of CF, the Schiller-Pisarev test and the Muhlemann-Cowell bleeding index, as well as absolute suppression of pathogenic microorganisms. Conclusion: The combinations of TDT with Soderm®-Forte gel and NIF of Rexod® in EP in rats can significantly increase the effectiveness of the treatment. The data obtained indicate the expediency of the administration of Soderm®-Forte gel, as well as its combination with NIF of Rexod® in dental practice in the complex therapy of patients with periodontitis.